Preparing Future Teachers to Manage Classroom Behavior: Evaluation of an Instructional Package Utilizing Mixed Reality Simulation - Walker, Heather E (ProQuest Dissertations & Theses, 2018)
Classroom management has been demonstrated to be a critical variable related to student outcomes; therefore, it should be treated as a core competency in teacher preparation. Evidence indicates there is a gap between how teachers are being prepared to manage classrooms and what they are experiencing once they enter the field as in-service teachers. A mixed method, quasi-experimental study was designed to evaluate the impact of an instructional package including TeachLivE™ on participants’ performance of two general classroom management strategies targeting disruptive student behavior. The study also looked at the feasibility of this type of instruction from a cost-benefit standpoint as well as the social validity of the practices implemented during the study. Participants included graduate and undergraduate students enrolled in a required course which covered topics related to teaching exceptional students in inclusive classrooms. Single subject data analysis demonstrated the impact of instruction across participants, statistical analysis was used to examine pre- and post-instruction measures, and qualitative data coding procedures were used to discover patterns in student responding on a social validity questionnaire and in weekly journal entries. Results indicated participants were able to perform components of two strategies following instruction; however, teacher self-efficacy measured by the TSES demonstrated no change. A brief cost-benefit analysis provided information on the feasibility of the program with respect to time and budgetary expenditures. Last, qualitative analysis indicated that participants view classroom management as critical and believe it is important to have opportunities to practice strategies prior to entering a classroom.